Ukrainian guidelines for the prevention and treatment of glucocorticoid-induced osteoporosis - N.V. Grygorieva; V.M. Kovalenko; М.О. Коrzh; M.D. Tronko; I.Yu. Golovach; N.V. Dedukh; D.G. Rekalov; S.S. Strafun; S.I. Smiyan; O.A. Golubovska; Ya.O. Dziublyk; N.V. Kharchenko; et al. (Bolʹ, Sustavy, Pozvonočnik)
Introduction. Glucocorticoid-induced osteoporosis (GIOP) is a bone metabolic disease that develops as a result of glucocorticoid (GC) use, is one of the most frequent causes of secondary osteoporosis, leads to an increase in the risk of low-energy fractures, disability and mortality of GC users. Despite the few studies conducted in Ukraine on the epidemiology and treatment of GIOP, there have been no national recommendations for its management until now, which has become the background for their creation. The purpose was to develop national guidelines for the diagnosis, prevention, and treatment of GIOP based on the analytical analysis of modern literary sources to improve the awareness of the medical community of Ukraine, improve management, and reduce the socio-economic burden of the disease. Materials and methods. A group of 18 experts, leading Ukrainian scientists in various fields, was created to develop the guideline. An analysis of current literary sources on epidemiology, risk factors, diagnosis, prevention and treatment of GIOP, and monitoring of the effectiveness and safety of its treatment was carried out. Evidence was synthesized using the GRADE system, and a critical assessment of the quality of the recommendations was carried out using the AGREE II tool. Results. The guideline consists of 12 provisions on screening, diagnosis, prevention, and treatment of GIOP. The authors emphasized the need to increase the awareness of the medical community of Ukraine regarding the problem, as well as patients regarding the possible side effects of GC. They presented the features of the clinical assessment of the osteoporotic fracture risk in GC users, as well as modern and available in Ukraine methods of diagnosis and treatment of GIOP. Conclusion. The first Ukrainian guideline for screening, diagnosis, prevention, and treatment of GIOP is an important national tool for its management, which is recommended by the Board of the Ukrainian Association of Osteoporosis for use in practical health care by doctors of various specialties.